Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2196/16211
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Digital Well-Being Intervention on Patients With Chronic Conditions: Observational Study

Abstract: Background Chronic conditions account for 75% of health care costs, and the impact of chronic illness is expected to grow over time. Although subjective well-being predicts better health outcomes, people with chronic conditions tend to report lower well-being. Improving well-being might mitigate costs associated with chronic illness; however, existing interventions can be difficult to access and draw from a single theoretical approach. Happify, a digital well-being intervention program drawing from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 83 publications
2
42
0
Order By: Relevance
“…Online health communities (OHCs) are internet-based platforms that allow people to connect over shared experiences and communicate about health [ 20 - 22 ]. OHCs are disrupting traditional hierarchies in the health care industry by offering what traditional health care cannot offer—conversations about the lived experiences of people with particular health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Online health communities (OHCs) are internet-based platforms that allow people to connect over shared experiences and communicate about health [ 20 - 22 ]. OHCs are disrupting traditional hierarchies in the health care industry by offering what traditional health care cannot offer—conversations about the lived experiences of people with particular health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research demonstrated that 8 weeks of Happify Health use improved subjective well-being among people with chronic physical conditions, including type 2 diabetes, at the same rate as people without these conditions [ 61 ]. However, the previous study examined the effects of Happify Health use on users with at least one self-reported chronic condition but was unable to examine the impact on users with specific chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our intervention may have weaker effects, particularly on diabetes-specific outcomes, than CBT modified for diabetes. However, there is preliminary evidence that completing regular activities (ie, not disease specific) on Happify Health is associated with improved subjective well-being among people with chronic physical conditions [ 61 ] and that mindfulness and PP interventions without behavioral strategies for managing diabetes can improve participants’ health outcomes [ 30 ]. If we are able to demonstrate that Happify Health use can have physical as well as psychological benefits for people with poorly managed type 2 diabetes and elevated depressive symptoms, without incorporating specific behavioral strategies for managing diabetes, the effects are also likely to have broader applicability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations